EVALUASI PROGRAM PRAKTIK INDUSTRI MAHASISWA PENDIDIKAN TEKNIK MESIN FKIP UNS PADA INDUSTRI OTOMOTIF MENGGUNAKAN MODEL CIPP - Adhi Wardhana; Muhammad Akhyar; Husin Bugis (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2022)
The objective of this research is to determi ne the quality of: (1) Context of the Industrial Practice Program, comprise (a) the objectives of Industrial Practices, (b) the vision and mission of the Study Program, (c) the condition of students, (d) the condition of the Study Program; (2) Input of the Industrial Practice Program, comprise (a) preparation before implementing of the Industrial Practices; (3) Process of the Industrial Practice Program, comprise (a) the role of students, (b) the role of supervisors, (c) the role of industry advisers, (d) the role of industry employees; (4) Product of the Industrial Practice Programs, comprise (a) student skills, (b) practical knowledge, (c) student personality, (d) innovative student experience, (e) student satisfaction, (f) industry satisfaction. The population of the research ware students of Mechanical Engineering of Education Study Program Sebelas Maret University and industry. The sample of the research using purposive sampling technique were automotive industry and automotive concentration students of mechanical engineering of education was implementing the Industrial Practice for 2017 and 2018 periods. This research using an evaluative method with CIPP (Context, Input, Process, Product) design. Data collection techniques using questionnaires and interviews. The validity technique in this research is logic validity. The data analysis technique of this research is average analysis which was assessed based on the research criteria. The results showed that: (1) Context of the Industrial Practice Program classified as high, comprise (a) the objectives of the Industrial Practice, (b) the vision and mission of the Study Program, (c) the condition of students, (d) the condition of the Study Program;(2) Input of the Industrial Practice Program classified as high, comprise (a) preparation before implementing of the Industrial Practices; (3) Process of the Industrial Practice Program classified as high, comprise (a) the role of students, (b) the role of supervisors, (c) the role of industry advisers,(d) the role of industry employees; (4) Product of the Industrial Practice Program classified as very high, comprise (a) student skills, (b) practical knowledge, (c) student personality, (d) innovative student experience, (e) student satisfaction, (f) industry satisfaction.